Reconstructive plastic surgery on the urinary tract of a kidney transplant - D. A. Saydulaev; V. S. Bogdanov; M. A. Petryaev; A. A. Kartashev; A. A. Zharikov; S. V. Sadovnikov; I. A. Miloserdov (Вестник трансплантологии и искусственных органов, 2021)
We present a clinical case of urolithiasis. A patient diagnosed with stage 5 chronic kidney disease due to autosomal dominant polycystic kidney disease after bilateral nephrectomy underwent kidney transplantation with ureteral graft stenting. Two months after the operation, a stone was found in the upper third of the ureteral graft, complicated by necrosis in this area. Reconstructive plastic surgery on the ureter of the transplanted kidney with removal of the ureteral stone achieved the desired clinical effect.